Three dimensional Reconstruction and finite element modelling of middle ear in the study of middle ear biomechanics for clinical applications - SANA, PARVEEN; SHRADDHA, JAIN (International Journal of Psychosocial Rehabilitation, 2020)
Three Dimensional Reconstruction and finite element modelling of middle ear in the study of middle ear biomechanics for clinical applicationsComputerised models are more commonly being used for understanding the acoustics of middle ear, pre-op planning and simulation of clinical situations, especially when dealing with tiny complex anatomical regions like the middle ear. One technique used to analyse the mechanics of complex models is the method of finite element model formation, whereby the system of interest is divided into varios number of small simple elements. (1-2)To study middle ear mechanics in normal stateTo study middle ear mechanics in diseased stateTo study the effect of various surgical interventions namely- mastoidectomy,grafting,tympanic membrane grafting, ossicular reconstruction as well as lowering of posterior canal wall- on middle ear biomechanics.(4)Building of a simple modelThe FE modelling approach will be divided into three parts:Computerised modelling of the geometry of middle ear (19)Construction of a working finite element model Calibration of the working model in real time with human ears to obtain the final finite element model. (3) Computerised geometric modelling by HRCT of temporal boneHRCT scan will be performed in this study , in a normal adult with no hearing loss and no other comorbidities. Ear examination and pure tone audiometry (PTA) will be performed prior to High Resolution CT scans. (18) Images of the temporal bone procured will be used for evaluation and reconstruction. This geometric model will be used to identify the characteristics of the middle ear. To conform the validity of the study , it will be compared with the published data.(3)We plan to devise a 3D model of the middle ear, which is made of smaller mesh particles, which vibrate with different frequencies, which is simple and mimicks the various pathological processes and reconstructive methods for clinical applications.(17)We also plan to study the effect of material properties of various graft materials used in various types of tympanomastoidectomy (8) non dynamic behaviours of the middle ear using the FE model. This would include TM thickness, thickness of graft in Short columella in Type – III tympanoplasty, Long Columella Type III tympanoplasty with cartilage, in canal wall down and canal wall up mastoidectomy, effect of middle ear volume, etc. (7) FE model will help in investigating the characteristics of the middle ear system and improving our understanding of its mechanical function. Furthermore, FE modelling of the middle ear would be used to simulate and evaluate the pathological changes in the conditions of middle ear disorders, like Tympanic membrane perforations, of different sizes and sites, tympanosclerosis, Middle ear fluid (8), ossicular discontinuity, Ossicular fixation.(16) It would be possible to predict how the function of middle ear is affected by different kinds of middle ear pathologies and to understand the differences in middle ear structures which can impact hearing function prior to surgery.